Integração e expressão do gene ltb-r1 em plantas de tabaco - Klafke, Gabriel Baracy (2010)
During the past decades, the development of genetically modified plants became a consolidated reality. Taking advantage of the genetic engineering process, it is possible to obtain modified plants to use as bioreactors in the production of tissue or organs expressing antigens which can be easily used as vaccines. The plant-based expression systems as tomato and lettuce, which attend as models for that process, present innumerous advantages such as conservation of eukaryotic machinery, which promote pos-translational modifications, possibility of large-scale production and development of safer and economically more attractive vaccines. Taking use of that strategy, the Swine mycoplasm hyopneumoniae (SMP) disease can be one important and possible target to either be eradicated or controlled. The SMP, caused by fastidious bacterium Mycoplasma hyopneumoniae, is one of the most important respiratory disease in swine breeding, due to its very high prevalence coupled with associated losses all over the whorld, and has in the recombinant DNA technology a viable alternative in the development of more effective and safe vaccines The objective of my work was to genetically manipulate tobacco plants in order to use them as bioreactor in the production of an antigen against PMS. Tobacco leaves and internodes were cultured in different concentrations of BAP and AIA hormones. The best regeneration results for both explants were seen with 1,5mg.L-1 BAP and 0,1mg.L-1 AIA. The selection test with the kanamycin antibiotic appeared to be highly effective, showing a total inhibition of regeneration with 30 mg.L-1 and 100 mg.L-1 for leaves and internodes respectively. The recombinant colonies of A. tumefaciens, containing ltb-r, were co-cultivated with the internodes and leaves from plants germinated in vitro. The next step, the explants were transferred to the selection medium in order to induce the selection of the putatively transformed cells. The genomic DNA from regenerated and putatively transformed plants were extracted and amplified by PCR, where it was detected the presence of a band referent to ltb r1. The analyses of the integration and the transcription of ltb-r1 were carried out by Southern blot and RT-PCR, respectively. In both techniques, it was possible to confirm the presence of one band which corresponds to the expected size of ltb-r1, supporting the integration and expression of the gene. However, with the tests used here, it was not possible to detect with accuracy the recombinant protein